Experimental study on impact failure characteristics of roadway with different ellipticity - Qingfeng XU; Shoujian PENG; Jiang XU; Yan YANG; Chaolong QIN; Xiaoli NONG; Li JIA (Meitan xuebao)
In order to study the influence mechanism of ellipticity on the impact damage characteristics of roadways, the multifunctional physical simulation test system for deep rockburst developed independently was used to carry out the impact damage test of elliptical roadways under the true three-dimensional conditions, and analyze the evolution law of impact damage of roadways with different ellipticity. The results show that: the peak stress and axial deformation of the sample will increase and then decrease with the increase of ellipticity, and the peak stress and axial deformation of the sample with an ellipticity of 1.25 is the largest; the damage of the roadway is mainly concentrated in the two sides of the side gangs, and the 3D localization of the acoustic emission verifies this kind of damage characteristic; the acoustic emission counts and energies of the perturbation loading period increase suddenly, and the b value of the acoustic emission decreases suddenly, which means that the sample produces the large-scale damage under the disturbing stress. large-scale damage. With the increase of ellipticity, the maximum counts, the maximum energy, and the decrease of b-value of the acoustic emission all show an increasing trend. The nonlinear relationship between the cumulative energy and time of the acoustic emission of the samples with different ellipticity proves the principle of sudden energy increase of impact damage. The infrared cloud map and average infrared radiation temperature of different ellipticity samples have obvious increase in damage, among which the ellipticity of 1.25 samples is the most significant. The test results provide theoretical support for the design of underground engineering roadway section to prevent rockburst.